2020
DOI: 10.1016/j.jcv.2020.104618
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of two SARS-CoV-2 IgG/IgM rapid tests (Covid-Presto and NG-Test) and one IgG automated immunoassay (Abbott)

Abstract: The aim of this study was to assess the analytical performances, sensitivity and specificity, of two rapid tests (Covid- Presto® test rapid Covid-19 IgG/IgM and NG-Test® IgM-IgG COVID-19) and one automated immunoassay (Abbott SARS-CoV-2 IgG) for detecting anti- SARS-CoV-2 antibodies. This study was performed with: (i) a positive panel constituted of 88 SARS-CoV-2 specimens collected from patients with a positive SARS-CoV-2 RT-PCR, and (ii) a negative panel of 120 serum samples, all collected before November 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 9 publications
5
20
2
Order By: Relevance
“…However, the Ag-source clearly appeared not to be the only factor attributing to diagnostic sensitivity ( Table 1 ). Our data are in concordance with other head to head SARS-CoV-2 antibody comparison studies ( Lassaunière et al, 2020 ; Van Elslande et al, 2020 ; National SARS-CoV-2 Serology Assay Evaluation Group, 2020 ; Pieri et al, 2020 ; Charpentier et al, 2020 ; Herroelen et al, 2020 ; Perkmann et al, 2020 ) and, if compared on the same level of specificity (95%), the R-N revealed the best overall sensitivity (84.0% [74.1–91.2]) versus DS-S the lowest (61.7% [50.3–72.3]). For symptomatic patients, all tests, except for TD-S, revealed a sensitivity of 100% ≥ 20 days after symptom onset ( Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, the Ag-source clearly appeared not to be the only factor attributing to diagnostic sensitivity ( Table 1 ). Our data are in concordance with other head to head SARS-CoV-2 antibody comparison studies ( Lassaunière et al, 2020 ; Van Elslande et al, 2020 ; National SARS-CoV-2 Serology Assay Evaluation Group, 2020 ; Pieri et al, 2020 ; Charpentier et al, 2020 ; Herroelen et al, 2020 ; Perkmann et al, 2020 ) and, if compared on the same level of specificity (95%), the R-N revealed the best overall sensitivity (84.0% [74.1–91.2]) versus DS-S the lowest (61.7% [50.3–72.3]). For symptomatic patients, all tests, except for TD-S, revealed a sensitivity of 100% ≥ 20 days after symptom onset ( Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…The sensitivity and specificity reported in our study for the NG-Test ® are lower than those reported in three recent publications [ 1 , 5 , 6 ], all conducted retrospectively on sera. One explanation for the lower sensitivity and specificity observed in our study relative to these three studies may be the different characteristics of the included participants: the vast majority of participants in our study were women <50 years of age, whereas the cases were mainly men over 50 in the other three studies (median age = 58 years for Dortet et al) [ 1 , 5 , 6 ]. In addition, the clinical presentation of COVID-19 was also different in our population: no HCWs required admission for COVID-19, whereas most participants in the three published studies were hospitalised (up to 82% in the study of Dortet et al) [ 1 , 5 , 6 ].…”
contrasting
confidence: 95%
“…This suggests that the NG-Test ® results for IgM must be interpreted with caution. This result is in accordance with that of the study of Charpentier et al [ 6 ], which reported lower specificity than the two other studies on sera.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These rapid assays provide a low-throughput antibody testing option for laboratories with limited resources and are particularly useful for epidemiologic field studies. However, a meta-analysis evaluating the diagnostic accuracy of SARS-CoV-2 serologic testing concluded that LFIAs were consistently less sensitive than ELISA or CLIA methods [ 9 ], and subsequent studies have reported a wide range of sensitivities and specificities [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. Nevertheless, the Infectious Diseases Society of America (IDSA) recommends against the use of IgG or IgM antibody combination tests, where detecting either antibody isotype is used to define a positive result [ 7 ].…”
Section: Introductionmentioning
confidence: 99%